Diagnostic Imaging in Intervertebral Disc Disease - da Costa, Ronaldo C.; De Decker, Steven; Lewis, Melissa J.; Volk, Holger; , The Canine Spinal Cord Injury Consortium (CANSORT-SCI); Moore, Sarah A.; Olby, Natasha J.; Levine, Jonathan M.; Lewis, Melissa J.; Jeffery, Nick D.; Mullins, Maureen E.; da Costa, Ronaldo C.; et al. (Frontiers in Veterinary Science, 2020)
Imaging is integral in the diagnosis of canine intervertebral disc disease (IVDD) and in differentiating subtypes of intervertebral disc herniation (IVDH). These include intervertebral disc extrusion (IVDE), intervertebral disc protrusion (IVDP) and more recently recognized forms such as acute noncompressive nucleus pulposus extrusion (ANNPE), hydrated nucleus pulposus extrusion (HNPE) and intradural/intramedullary intervertebral disc extrusion (IIVDE). Many imaging techniques have been described in dogs with roles for survey radiographs, myelography, computed tomography (CT) and magnetic resonance imaging (MRI). Given how common IVDH is in dogs, a thorough understanding of the indications and limitations for each imaging modality to aid in diagnosis, treatment planning and prognosis is essential to successful case management. While radiographs can provide useful information, especially for identifying intervertebral disc degeneration or calcification, there are notable limitations. Myelography addresses some of the constraints of survey radiographs but has largely been supplanted by cross-sectional imaging. Computed tomography with or without myelography and MRI are currently utilized most widely and have become the focus of most contemporary studies on this subject. Novel advanced imaging applications are being explored in dogs but are not yet routinely performed in clinical patients. The following review will provide a comprehensive overview on all available imaging modalities reported to aid in the diagnosis of IVDH including IVDE, IVDP, ANNPE, HNPE and IIVDE.